Use of water retention polymers during implementation of coffee plantations - Pieve, Leonardo Miari; Guimarães, Rubens José; Assis, Gleice Aparecida; Silva Amato, Gabriel Augusto; Corrêa, Juliano Miari (Coffee Science - ISSN 1984-3909, 2014)
The use of water retention polymers may be an option for ensuring water availability during the implementation phase of the coffee plantation. The experiment was conducted at Capao dos Oleos, Coqueiral municipality, Minas Gerais, in the period from 2009 to 2011. The aim of this study was to evaluate the effects of the water-retaining polymer which was previously hydrated for a better water supply, seeking to improve the survival and growth of coffee plants during the implementation phase of the culture in the field. A randomized block design was used in a factorial 4x3x2 was used with an additional treatment with four replications, totaling 25 treatments and 100 plots. Treatments consisted of four doses, three volumes and two areas of application of water retention polymers, plus an additional treatment as a control without the use of hydrogel. Growth evaluations were conducted in February 2010 and February 2011. The best form of application of the polymer was in the planting hole at the volume of 1.5 liters of solution composed of 1.5 kg of polymer diluted in 400 liters of water. After 476 days of the crop implementation there was no effect of the polymer application with a single dose on growth and survival of trees, opening up the discussion of possible viability of the reapplication of water retention polymers after crop implementation.